Prevalence of chronic hepatitis B in Oro Province, Papua New Guinea - Alice Unah Lee; Luke Mair; Bob Kevin; Lily Gandi; Olive Tarumuri; Caroline Lee; Sue Huntley; David Carl Hilmers (World Health Organization Regional Office for the Western Pacific, 2020)
Chronic hepatitis B (CHB) affects over 250 million people worldwide. In Papua New Guinea (PNG) CHB prevalence has been estimated to be over 8% and is a leading cause of death. To address this problem, an alliance between the government of Oro Province, a large private employer, and an Australian non-governmental organization was formed which established a CHB test and treat program. Between 2014 and 2019, rapid hepatitis B surface antigen testing on 4068 individuals in Oro Province was performed. The crude prevalence rate was 12.98% and was significantly higher in males (15.26%) than females (10.94%) (p<.001). The rate among children 10 years and under was 4.72%, 12.81% among women of childbearing age (19 to 35 years), and 18.48% in health care workers. These results indicate the need for improved birth-dose vaccination rates and immunization/treatment of women of childbearing age and health care workers to prevent transmission of CHB.